The Influence of Perceived Organizational Support And Emotional Intelligence on Work-Life Balance of Millennial Employees - Sakti Nofriyaldi; Abdhy Aulia Adnans; Siti Zahreni (Dinasti International Journal of Education Management And Social Science, 2024)
: The demographic bonus currently occurring in Indonesia is filled by the millennial generation. This millennial generation also makes up the majority of workers in companies today. The majority of millennials who currently fill the industrial world have several challenges in meeting their work demands. Some of these challenges include difficulties in fulfilling their roles in work and personal life. Therefore, this research aims to determine the influence of perceived organizational support and emotional intelligence on the work-life balance of millennial employees. The method used in this research is a quantitative method. The subjects in this research were 305 millennial employees. The measuring instruments used in this research are the perceived organizational support scale, emotional intelligence scale, and work-life balance scale. Data analysis was carried out using multiple regression statistical methods. The results of this research show that there is a positive and significant influence of perceived organizational support on the work-life balance of millennial employees, then there is a positive and significant influence between emotional intelligence and work-life balance of millennial employees, and there is a positive influence between perceived organizational support and emotional intelligence towards work-life balance of millennial employees with an effective contribution of 75.3%. It is hoped that the results of this research can be a reference for companies to retain employees and take advantage of employees' emotional intelligence abilities in balancing their roles in work and personal life, which can ultimately achieve work-life balance.